Idiopathic Isolated Acquired Steroid Dependent SO Palsy: A Rare Case Report - Isha Agarwal; Mayuresh Naik; HarinderSingh Sethi (Case Reports in Ophthalmological Medicine)
15-year-old boy presented with sudden onset, stable, nonprogressive painless diplopia (greatest in right gaze and inferior field of view) and hyperdeviation of left eye for a year. On ophthalmic examination, the patient had uncrossed diplopia with tilt and separation maximum in dextrodepression. On Park’s three step test, left eye hypertropia increased on right gaze and left tilt suggestive of left superior oblique (SO) palsy. On prism bar cover test (PBCT), deviation was more than 25 PD base-down over the left eye for both distance and near in all gazes. MRI head and orbit revealed a normal study while the myasthenia and inflammatory work-up was unremarkable. A provisional diagnosis of “Idiopathic Acquired Left Superior Oblique Palsy” was made and the patient was given trial of oral steroids at 1 mg/kg body weight. At 6 weeks, patient’s diplopia resolved and PBCT neutralised at 6PD. Oral steroids were gradually tapered off by 10 mg per week with weekly follow-up. Upon decreasing the dose of prednisolone to 5 mg, intermittent diplopia and 18 PD left hypertropia reappeared. When patient was again restarted on oral steroids at 1 mg/kg body weight, diplopia-hypertropia disappeared at 10 mg OD prednisolone only to reappear at 5 mg OD dosage, leading to the final diagnosis of a “Steroid Dependent Isolated Superior Oblique Palsy”. Presently, the patient is maintained on a daily dose of 10 mg oral prednisolone.